La collana longobarda / Maria Grazia Di Bernardo. - Di Bernardo, Maria Grazia (Imparare leggendo., 2010)
Who would believe that a study-trip to Italy could result in a passionate adventure? Anna, a German student, discovers a diary in her room, and decides to investigate it with the help of her friend Guido, a policeman. One of a series of original stories interspersed with exercises and illustrations designed to improve reading and speaking skills.